1999
DOI: 10.1002/(sici)1097-0096(199910)27:8<440::aid-jcu5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal sonographic diagnosis of ectopia cordis

Abstract: Purpose We present a small series of prenatally diagnosed cases of ectopia cordis. Methods Four fetuses with prenatally diagnosed ectopia cordis were sonographically evaluated and followed up. Results The fetuses were diagnosed with ectopia cordis at 9, 13, 21, and 29 weeks' menstrual age. The case diagnosed at 9 weeks is the earliest prenatal diagnosis reported, to our knowledge. The diagnoses were based on the demonstration of a fetal heart outside the thoracic cavity with Doppler waveforms typical of intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Similarly, Desselle et al suggested that the correlation between 2D and 3D examination is useful in surgical management in such newborns ( 2 ). The earliest prenatal diagnosis of CS is reported to have been established between 9 and 11 gestational weeks ( 18 , 19 ). Unfortunately, in our case, the thoracic wall defect was suspected only at 35 gestational weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Desselle et al suggested that the correlation between 2D and 3D examination is useful in surgical management in such newborns ( 2 ). The earliest prenatal diagnosis of CS is reported to have been established between 9 and 11 gestational weeks ( 18 , 19 ). Unfortunately, in our case, the thoracic wall defect was suspected only at 35 gestational weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This series documents three cases of ectopia cordis detected before 9 weeks of gestation. According to a recent review of the literature describing 17 cases of ectopia cordis diagnosed in the first trimester, the earliest diagnosis was made at 9 weeks in an embryo with a CRL of 28 mm . Our three cases were detected even earlier, in embryos with CRLs ranging from 10 to 21 mm.…”
Section: Early Sonographic Diagnosis Of Ectopia Cordis: Clinical Casesmentioning
confidence: 74%
“…Pentalogy of Cantrell remains a disease with poor prognosis; nonetheless, survival to adulthood with mild thoracoabdominal abnormalities has been reported. Patients with both PC and EC have even worse prognosis [3]. Less than 5% of patients with isolated EC survive [7].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although not part of the classic PC, some severe cases have been associated with herniation of the heart through the diaphragmatic defect, resulting in ectopia cordis (EC) [2]. Such a diagnosis carries a disastrous prognosis without surgical correction or palliation [3]. Furthermore, miscellaneous intracardiac abnormalities even worsen the survival.…”
Section: Introductionmentioning
confidence: 99%